2021
DOI: 10.3390/ijms22052268
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Critical Determinants of ACE2–SARS CoV-2 RBD Interaction

Abstract: Despite sequence similarity to SARS-CoV-1, SARS-CoV-2 has demonstrated greater widespread virulence and unique challenges to researchers aiming to study its pathogenicity in humans. The interaction of the viral receptor binding domain (RBD) with its main host cell receptor, angiotensin-converting enzyme 2 (ACE2), has emerged as a critical focal point for the development of anti-viral therapeutics and vaccines. In this study, we selectively identify and characterize the impact of mutating certain amino acid res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…The nanoluciferase complementation assay has been previously described in refs. 24 , 25 We tested the impact of atovaquone on SARS binding to ACE2 using a variety of plasmid constructs, notably the RBD or S1 domain from SARS-CoV2 or the RBD domain from SARS-CoV1 as described. 24 , 25 Following plasmid transfection using a PolyJet transfection reagent (SignaGen Laboratories) in HEK293, cells were lysed in a NanoLuc-compatible passive lysis buffer (Promega) and the lysate was dispensed into a 384-well plate to which atovaquone was added at a final concentration of 4 μM.…”
Section: Methodsmentioning
confidence: 99%
“…The nanoluciferase complementation assay has been previously described in refs. 24 , 25 We tested the impact of atovaquone on SARS binding to ACE2 using a variety of plasmid constructs, notably the RBD or S1 domain from SARS-CoV2 or the RBD domain from SARS-CoV1 as described. 24 , 25 Following plasmid transfection using a PolyJet transfection reagent (SignaGen Laboratories) in HEK293, cells were lysed in a NanoLuc-compatible passive lysis buffer (Promega) and the lysate was dispensed into a 384-well plate to which atovaquone was added at a final concentration of 4 μM.…”
Section: Methodsmentioning
confidence: 99%
“…We found that there were slight differences of the neutralizing activity among the three groups (RBD/hACE2, RBD/Non-hACE2, and Non-RBD) of spike mutants but were insignificant (Figure 4). It was accepted that the mutations located in the RBD/hACE2 region more likely alter the viral neutralization reactivity to antibodies (20). Our results of the neutralization of the convalescent plasma against different spike variants indicated that mutations in either RBD/hACE2 or RBD/Non-hACE2 interaction regions slightly decreased the neutralizing activity of the convalescent plasma against the corresponding pseudoviruses.…”
Section: Discussionmentioning
confidence: 63%
“…We also used a concatenated alignment with four ACE2 regions containing residues involved in binding to S protein of SARS-CoV-2 (Supplementary file 1 ). ACE2 binding regions that encompass the key residues enabling interactions with SARS-CoV-2 S protein were based on previous studies (Shang et al 2020 ; Brown et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%